2019
DOI: 10.1177/0300060519875857
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the incidence of cerebrospinal fluid leakage and residual tumors between functional and nonfunctional pituitary adenomas treated by endoscopic transsphenoidal pituitary adenomectomy

Abstract: ObjectiveThis study compared the incidence of cerebrospinal fluid (CSF) leakage and residual tumors between functional and nonfunctional pituitary adenomas treated with the endoscopic endonasal transsphenoidal approach (EETA).MethodsAll patients underwent endocrine examinations and brain magnetic resonance imaging before and after surgery. The length of admission, incidence of central diabetes insipidus, incidence of CSF leakage, symptom relief, and presence of residual tumors were compared between patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The rates of postoperative CSF leakage in our study seem to be high from an international perspective. However, the frequency of CSF leak varied over the years and in more recent years, our rates were comparable to those published from other high-volume centers [12,24]. Several studies have indicated an advantage of using a multidisciplinary team consisting of rhinologists and neurosurgeons when performing endoscopic approach to the sellar region [23].…”
Section: Discussionsupporting
confidence: 75%
“…The rates of postoperative CSF leakage in our study seem to be high from an international perspective. However, the frequency of CSF leak varied over the years and in more recent years, our rates were comparable to those published from other high-volume centers [12,24]. Several studies have indicated an advantage of using a multidisciplinary team consisting of rhinologists and neurosurgeons when performing endoscopic approach to the sellar region [23].…”
Section: Discussionsupporting
confidence: 75%
“…There were not enough studies to evaluate the influence of age ( 10 , 25 , 26 , 28 ), tumor pathological type ( 18 , 29 ), and experience of the surgeon ( 18 ), combined with other intracranial diseases ( 23 , 30 ), albumin level ( 17 ), chronic respiratory disease ( 16 ), and diabetes mellitus ( 10 ).We can only conduct qualitative analysis based on the literature (detailed information shown in Table 3 ).There was no significant statistical difference in the impact of gender on postoperative CSF leakage.…”
Section: Resultsmentioning
confidence: 99%
“…Hannan proposed that adrenocorticotropic hormone adenoma is a risk factor for cerebrospinal fluid leakage, due to centripetal obesity and higher BMI in patients with Cushing’s disease ( 18 ).While, Lee believed that nonfunctional pituitary macroadenoma was a risk factor, for the large tumor size. We need more clinical studies to confirm it ( 29 ).…”
Section: Discussionmentioning
confidence: 99%